Hukum Waris Adat Minangkabau dalam Pespektif Islam - Rizky Romadhan; Ade Ariana; Nurhafasah; Dwi Noviani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research explores Minangkabau customary inheritance law in the context of an Islamic perspective. In this context, there are two different inheritance law systems, namely customary inheritance law which developed in indigenous communities and Islamic inheritance law which is based on sharia principles. This research aims to identify points of similarity and difference between the two systems, as well as to reveal how customary inheritance law can play a role in the context of Islamic values. By analyzing the literature and analysis, this research provides a deeper understanding of how Padang traditional inheritance law can be understood within the framework of Islamic law. Customary inheritance law is a local law in a particular region or tribe that is valid and still implemented where traditional values ​​can be in line with Islamic principles. This shows that customary inheritance law can play an important role in strengthening Islamic values ​​in society. This research has practical implications in the context of law enforcement and community development. By understanding the role of customary inheritance law from an Islamic perspective, policy makers and legal practitioners can develop a more holistic approach in dealing with inheritance issues in multicultural societies.